Exploring the use of the Quake Safe House video game to foster disaster and disaster risk reduction awareness in museum visitors. (January 2021) - Gampell, Anthony Viennaminovich; Gaillard, J.C.; Parsons, Meg; Le Dé, Loïc
Abstract: This paper provides valuable insights into the use of disaster video games in museums. It contributes not only towards a better understanding of disasters within popular culture but also in fostering greater museum visitor participation in learning about disaster and disaster risk reduction (DRR). The theoretical background of this study draws on various scholarships from video game research, constructivist learning theory, and the museum learning environment. This research was undertaken in two New Zealand museums (Te Papa in Wellington and Quake City in Christchurch) which housed the disaster video game Quake Safe House (QSH). The research findings and associated discussion considers the potential of QSH to build disaster awareness based upon participants' gameplay. Ultimately, it is demonstrated that the use of 'serious' disaster video games, such as QSH, cannot be a stand-alone item for the purpose of learning within a museum space. Instead, such video games require better integration within the museum's environment and educational disaster displays to encourage and foster the participation of museum visitors in learning about disaster and DRR through multiple mediums.